ABORTUS - Dautović, Ferid (Novi Muallim, 2003)
"Sretna porodica" priredio: Halid Hasan Ali, El-'alemu 'l-islami, petak, 18. džumadel-ula 1421. h.g. /18. avgusta 2000. br. 1663 .. Prijevod s arapskog: Ferid Dautović